Studies in Colombian Ensifera and adjacent countries: New taxa of smallest field crickets (Orthoptera: Gryllidae: Gryllinae) - Cadena-Castañeda, Oscar J.; Orejuela, Mery Helen Tíjaro (Zootaxa, 2020)
Atsigryllus sikuani n. gen et n. sp. and Perugryllus ranoredium n. sp., tiny field crickets from the Orinoquian and Colombian Amazon respectively, are described. The diversity and distribution of field crickets for Colombia is discussed.